Editorial: Food safety in low- and middle-income countries - Grace, Delia; Bonfoh, B.; Häsler, B.; Hung Nguyen-Viet (Frontiers Media, 2024)
This is the first special edition on food safety in informal markets in low-and-middle income countries (LMICs). Despite their important public health and socio-economic impacts, foodborne diseases have only recently gained the attention of development institutes and initiatives (Grace, 2023). The is the result of growing appreciation of the enormous burden of foodborne disease in LMICs: the health burden is comparable to that of malaria, HIV/AIDs or tuberculosis and the economic cost is more than 100 billion USD a year (Havelaar et al., 2015; Jaffee et al., 2019). Most of the burden is caused by microbial and parasitic infections and most of these are acquired from fresh foods purchased in mass domestic markets in LMICs (Grace, 2015).